PENGARUH JUMLAH BAHAN BAKU, JAM KERJA TENAGA KERJA DAN JAM KERJA MESIN TERHADAP JUMLAH HASIL PRODUKSI TEPUNG TAPIOKA PADA PT. BUMI SARI PRIMA, PEMATANGSIANTAR - RAFIKA DEVI SARAGIH; RAHIM MATONDANG; MUSLICH LUFTI (JURNAL ILMIAH KOHESI, 2018)
In supply link point of view, a supplier plays an important role in raw material distribution; the scarcity of raw material distribution will bring about the risk for the disturbance in the amount of tapioca production. One of the reasons of the lack of cassava supply is that many cassava farmers postpone harvesting the cassava because they are busy by the end of year. Since cassava does not decompose easily, the farmers are not bothered when they postpone harvesting the cassava. The objective of the research was to find out and to analyze the influence of the number of raw materials, workers’, working hours, and working hours of machines on the amount of production. The research used explanatory research method. The data were gathered by using time series which were obtained from the report of the production within three consecutive years and were analyzed by using multiple regression analysis with an SPSS software program. The result of the research showed that (a) the number of raw materials had positive and significant influence on the amount of tapioca production, (b) workers’ working hours had positive but insignificant influence on the amount of tapioca production, (c) working hours of machines had negative and insignificant influence on the amount of tapioca production, and (d) the number of raw materials, working hours of workers, and working hours of machines simultaneously had positive and significant influence on the amount of production.